THE PREVALENCE OF INCIDENTAL NON-CORONARY FINDINGS IN 64 SLICE MULTIDETECTOR COMPUTED TOMOGRAPHY ANGIOGRAPHY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In order to evaluate obstructive coronary artery disease, computed tomography angiography is increasingly used for noninvasive coronary angiography. This technique gathers information about the coronary arteries as well as other organs that are irradiated but not typically evaluated, such as the heart, parts of the lungs, bony thorax, breasts, and upper abdomen. The purpose of this research is to determine how often non-coronary discoveries occur during 64-slice multi-detector computed tomography non-invasive coronary angiography procedures. Methods: From April 2013 to January 2015, a retrospective study was conducted at AL-Sader Medical City on a total of 200 cases. The patients were referred for a coronary computed tomography angiography on a 64-slice MDCT scanner. The participants' ages ranged from 55.5 to 60.5 years. From the carina level to somewhat below the diaphragm, the scans were obtained. A wide field of view (> 300 mm), including the whole thorax, was used during image reconstruction in order to assess incidental non-coronary abnormalities. Through the use of the mediastinal, lung, and bone windows, images were examined in the axial, coronal, and sagittal planes. The results showed that out of 200 patients, 30 percent had non-coronary abnormalities that were discovered by accident. There were 60 incidental non-coronary findings in total. The most common structure with incidental findings was the lung parenchyma, with 26 lesions (43.3%) reported there. The next most common structure was the mediastinal lymph nodes, with 11/60 (18.3%) reported there. The liver and pericardium each had 4 lesions (6.7%), and the aorta had 3 lesions (5%). The aortic valve, breasts, diaphragm, and vertebral body each had only 2 lesions (3.4%). The pleura, pulmonary artery, and other areas each had a single lesion, accounting for 1.7% of the total. Conclusion: Further work-up may be necessary for extra-coronary pathology; multidetector computed tomography coronary angiography and cardiac imaging can both give valuable information in this regard. As a result, regular clinical evaluations should include a comprehensive assessment of all organs shown in the scan.